ANALISIS PENGARUH PERKEMBANGAN FINTECH DAN E-COMMERCE TERHADAP PEREKONOMIAN MASYARAKAT - Nurcahya, Yulida Army; Dewi, Rizky Puspita (JAB (Jurnal Akuntansi & Bisnis), 2019)
ABSTRACTThe purpose of this paper is to see the development of technology into fintech and e-commerce in people's lives. The development of financial technology in Indonesia is increasing, but there are still many people who have not been served and use information technology technology. Basically fintech will facilitate the public to access various products in the financial sector and facilitate transactions by increasing financial literacy. Data collection methods used were interviews. From the results of the interview, the development of technology has not really influenced people's lives. They are still attached to the traditional culture, people do not agree with online loans because they consider the risk is greater than offline loans. More of them are already using e-commerce services.Keywords: fintech, online, e-commerce